Patterns of Peer Social Support in Maintaining the Psychological Well-being of Students at MAN 1 Banyumas - Arundaya Nara Tisna; Muh. Hanif (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Patterns of peer social support in maintaining the psychological well-being of students at MAN 1 Banyumas are examined in relation to adolescent vulnerability to academic pressure, social adjustment challenges, and personal problems that require continuous emotional buffering in school life. Adolescence represents a critical developmental stage in which peer relationships become central to daily coping and emotional regulation within the madrasah environment. A qualitative case study approach was employed, with data collected through observation, in-depth interviews, and documentation. Findings show that peer social support operates through emotional assistance, academic collaboration, informational exchange, and companionship, enabling students to manage stress and interpersonal conflict more effectively. Peer networks also function as informal pathways that often precede formal counseling access, highlighting their structural importance in help-seeking behavior. Although positive peer relations strengthen psychological well-being and classroom climate, closed friendship groups may restrict broader social interaction and occasionally generate minor conflict. Overall, peer social support constitutes a key relational mechanism in sustaining students’ psychological well-being and fostering supportive school environments.